Investigation of the influence of minor components and fatty acid profile of oil on properties of beeswax and stearic acid-based oleogels - Sivakanthan, S.; Fawzia, S.; Mundree, S.; Madhujith, T.; Karim, A. (Elsevier, 2024)
Understanding the impact of minor components and the fatty acid profile of oil on oleogel properties is essential for optimizing their characteristics. Considering the scarcity of literature addressing this aspect, this study aimed to explore the correlation between these factors and the properties of beeswax and stearic acid-based oleogels derived from rice bran oil and sesame oil. Minor oil components were modified by stripping the oil, heating the oil with water, and adding β-sitosterol. Oleogels were then prepared using a mixture of beeswax and stearic acid (3:1, w/w) at a concentration of 11.74 % (w/w). The properties of oils and oleogels were evaluated. The findings indicated that minor components and fatty acid composition of the oils substantially influence the oleogel properties. Removing minor components by stripping resulted in smaller and less uniformly distributed crystals and less oil binding capacity compared to the oleogels prepared from untreated oils. A moderate amount of minor components exhibited a significant influence on oleogel properties. The addition of β-sitosterol did not show any influence on oleogel properties except for the oleogel made from untreated oil blend added with β-sitosterol which had more uniform crystals in the microstructure and demonstrated better rheological stability when stored at 5 ◦C for two months. The oil composition did not show any influence on the thermal and molecular properties of oleogels. Consequently, the oleogel formulation derived from the untreated oil blend enriched with β-sitosterol was identified as the optimal formula for subsequent development. The findings of this study suggest that the physical and mechanical properties as well as the oxidative stability of beeswax and stearic acid-based oleogels are significantly affected by the minor constituents and fatty acid composition of the oil. Moreover, it demonstrates that the properties of oleogels can be tailored by modifying oil composition by blending different oils.
Keywords: Minor components; Beeswax; Stearic acid; Fatty acid composition